Performance evaluation of routing protocols in vehicular ad-hoc networks. (18th November 2005) - Santos, R.A.; Edwards, A.; Edwards, R.M.; Seed, N.L.
This paper presents a reactive location routing algorithm that uses cluster-based flooding for Vehicular Ad-hoc Networks (VANET). We compare both position-based and non-position-based routing strategies in typical urban and motorway traffic scenarios. A microscopic traffic model, developed in OPNET, is used to evaluate the performance of the Location Routing Algorithm with Cluster-Based Flooding (LORA_CBF), Ad-Hoc On-demand Distance Vector (AODV) and Dynamic Source Routing (DSR) in terms of average Route Discovery (RD) time, End-to-End Delay (EED), Routing Load, Routing Overhead, Overhead, and Delivery Ratio.